ダイ46ジ ナンキョク チイキ カンソクタイ リュツォ・ホルムワン , プリンスオラフ カイガン オヨビ ニシ エンダビーランド チシツ・コチジキ カキ ヤガイ チョウサ ホウコク 2004-2005 - 本吉, 洋一; モトヨシ, ヨウイチ; 廣井, 美邦; ヒロイ, ヨシクニ; Satish-Kumar , M.; 加々島, 慎一; カガシマ, シンイチ; 隅田, 祥光; スダ, ヨシミツ; 石川, 尚人; イシカワ, ナオト; Motoyoshi, Yoichi; et al. (2006)
P(論文) 第46次南極地域観測隊は,リュツォ・ホルム湾,プリンスオラフ海岸及び西エンダビーランドの露岩域を対象に,2004年12月17日から2005年2月17日にかけて地質・古地磁気野外調査活動を行った.この観測は,南極地域観測第VI期計画のプロジェクト研究観測「南極域から探る地球史」の中の「東南極リソスフェアの構造と進化の研究II」の一環として計画立案されたものである.第46次夏期観測では野外観測支援のための小型ヘリコプターが導入され,「しらせ」搭載ヘリコプターとともに野外調査の支援作業にあたった.ここでは,観測計画を実施するための,主に設営面での計画,準備,そして活動経過と問題点について報告する. The 46th Japanese Antarctic Research Expedition (JARE-46) conducted field operations on geological and paleomagnatic studies in the regions of Lutzow-Holm Bay, Prince Olav Coast and western Enderby Land during December 17, 2004 through February 17, 2005, under a part of the SEAL II (Structure and Evolution of East Antarctic Lithosphere II) project. A small helicopter was used to support field parties during the summer operations conducted by JARE-46. This report summarizes preparations for field operations and activities of the geological and paleo-magnetic team, and points out some problems for the future planning. departmental bulletin paper